Reforming men: Pentecostalism and masculinity in Papua New Guinea - Eves, Richard (The Australian journal of anthropology, 2016)
The basic premise of this paper is that oppressive and violent behaviour is not an essential aspect of the male identity. Seeking to comprehend the underlying causes of violence, specifically against women but also more generally, this paper examines some of the alternative ways of being a man that have accompanied Christianity. Through observation of some Pentecostals from New Ireland, I have concluded that new ways of being a man that are less oppressive and dominating for women are emerging. This phenomenon I argue is a step towards gender equality, since it involves creating more caring and equitable relationships and a step towards reducing violence both against women and in the community, since it embraces non-violent ways of being a man. Particularly useful in analysing the process of reforming men is Foucault's work on governmentality since it relates well to the Pentecostal emphasis on radical change in being ‘born again’. Conversion for born-again Christians is more than simply abandoning sin; rather it involves the creation of a new self and becoming a new person. Similarly, Foucault argues that the individual practises the art of self-governance in re-forming her or himself as she or he desires.